OBSERVATION ON THE SEASONAL PRAWN FISHERY OF THE PERIATHALAI COAST IN THE GULF OF MANNAR - Rajamani, M; Manickaraja, M (Indian Journal of Fisheries, 2011)
The seasonal prawn fishery of Periathalai, a fishing village on the south-east coast of Tamil Nadu, lasts for a period of three to four months in a year. The fishery was constituted exculsively by Penaeus indicus. During the three year period from 1985 to 1987 the estimated catch of P. indicus ranged between 95.9 and 106.7 tonnes and the maximum catch was recorded in the month of July. There was a gradual decrease in the female population. Mature and spent-recovering females formed major portion whereas immature females were seldom recorded in the catches